Twofold C–H Functionalization: Palladium-catalyzed ortho Arylation of Anilides - Brasche, Gordon (2008)
The ortho arylation of anilides to form biphenyls via a twofold C–H functionalization/C–C bond-forming process is described. The oxidative coupling takes place in the presence of 5–10 mol % Pd(OAc)(2), 10–20 mol % DMSO, and 4–11 equivalents of the aryl substrate in TFA under an oxygen atmosphere. No metal-containing co-catalyst is required.